Development Strategy of Kurma Park Agrotourism Based on Local Community Empowerment in Pasuruan Regency - Ridwan, Muhammad; Mubarokah, Mubarokah; Roidah, Ida Syamsu (Kadiri University - Faculty of Agriculture, 2025)
Kurma Park Agrotourism is the first date plantation-based artificial tourism in Indonesia. The problem is that the contribution of the number of visitors to Kurma Park Agrotourism to Pasuruan is very low, namely 0.87%. The main focus of this research is to formulate a development strategy for Kurma Park Agrotourism based on local community empowerment. The total respondents of this study were 113 respondents including 4 managers, 12 (Micro, Small and Medium Enterprises) MSMEs, and 97 visitors. The data analysis method used is descriptive analysis, (Strengths, Weaknesses, Opportunities, and Threats) SWOT and (Quantitative Strategic Planning Matrix) QSPM. The results showed that Kurma Park Agrotourism is in quadrant 2. Hence, the strategy that needs to be applied is the S-T (Strengths Threats) strategy, which shows that although Kurma Park Agrotourism faces various threats, Agrotourism still has strengths from an internal perspective. The strategy that must be applied is to use strengths to take advantage of long-term opportunities using a diversification strategy. There are 5 implications of development strategies that can be carried out by Kurma Park Agrotourism, namely 1) Development of community-based tourism in tourism management. 2) Diversification of processed date products and development of tourism concepts. 3) Development of a sustainable agricultural system. 4) Integrating destinations with exclusive package tours and 5) Increasing digital-based tourism services. The results of this study are expected to provide recommendations for innovative development strategies to increase tourist visits to Kurma Park Agrotourism and have a positive impact on improving the economy of the surrounding community